Gambaran Pengetahuan dan Sikap Ibu serta Peran Kelompok Pendukung ASI terhadap Pemberian ASI Eksklusif (Studi Kasus di Desa Kekeran Kecamatan Mengwi) - Putu Sannia Dewi; Anak Agung Ayu Lila Paramasatiari; I Wayan Darwata (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
Exclusive breastfeeding is not giving other food or drink (including water) to the baby for six months. From the predetermined target (60%), the coverage of exclusive breastfeeding at the Mengwi I Health Center was 53.69% (2019). This figure changes each year, so improvements in nutritional status must be carried out and maintained continuously. In order to realize the exclusive breastfeeding target of 60%, the government has provided many programs, one of which is the Breastfeeding Support Group (KP-ASI). KP-ASI is a group of pregnant women who exchange information to optimize breastfeeding. Based on the 2019 activity report in Kekeran Village, Mengwi I Health Center, the intensity of breastfeeding has increased from 87% to 96%. This study was done to describe the knowledge and attitudes of mothers and the role of KP-ASI in exclusive breastfeeding in Kekeran Village, Mengwi District. The design of this research is descriptive quantitative with case study method. The population is the mothers of KP-ASI participants in Kekeran Village, Badung Regency. The results showed that all subjects in this study (100.0%) generally had a good knowledge of exclusive breastfeeding. Most of the subjects in this study had a good attitude in exclusive breastfeeding, as many as 18 people (66.7%). Most of the subjects in this study have a good role of KP-ASI, as many as 26 people (96.3%).